Predicting short-term (30-day) mortality in patients with ischemic stroke using the baseline score of the National Institutes of Health Stroke Scale: Lestvica NIHSS (National Institutes of Health Stroke Scale) in kratkoročna (30-dnevna) umrljivost bolnikov z ishemično možgansko kapjo - Hojs Fabjan, Tanja (Acta Medico-Biotechnica, 2021)
Purpose: The National Institutes of Health Stroke Scale (NIHSS) was developed to measure neurologic outcome and recovery in patients with stroke. The aim of our study was to establish the validity of the NIHSS on short-term (30-day) mortality in patients with ischemic stroke.Methods: All 402 patients (216 males) with acute ischemic stroke hospitalized over 1 year were included in the study. Information on the presence of diabetes mellitus and smoking habits was obtained by a questionnaire. Systolic and diastolic blood pressure was measured upon hospital admission. The body mass index was calculated. Laboratory data were assessed in the first 24h after stroke onset. The National Institutes of Health Stroke Scale (NIHSS) was employed upon hospital admission. Patients were then followed up for 30 days.Results: The mean age of patients was 70.89 years (range, 36–96 years). Women were older than men (P
Keywords: schemic stroke; NIHSS; short-term mortality